1979
DOI: 10.1203/00006450-197906000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity Related to Sodium Balance, Renal Function and Urinary Vasopressin in the Newborn Infant

Abstract: Summary MATERIALS AND METHODSPlasma renin activity was determined in 25 healthy, full-term, newborn infants aged 1 day to 9 weeks. High values were found, the mean level at 1-2 days of life (24.8 +. 8.4 ng/ml/hr, SE) being significantly higher than the mean levels at 7-9 days (5.8 + 1.5) and at 4-9 weeks (8.1 f 13) (P < 0.05). No correlation was found between plasma renin activity and systolic blood pressure, hematocrit, creatinine clearance, serum sodium, or serum potassium. Plasma renin activity (log values)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The renal handling of AVP has been studied extensively, and there is considerable evidence that glomerular filtration is the primary source of urinary AVP in the adult (23) and normal term infant beyond the second day (24). Furthermore, it has been shown that AVP is neither secreted nor destroyed by the renal tubules (25) and that AVP in adult urine is stable over long periods of time (1 9).…”
Section: Discussionmentioning
confidence: 99%
“…The renal handling of AVP has been studied extensively, and there is considerable evidence that glomerular filtration is the primary source of urinary AVP in the adult (23) and normal term infant beyond the second day (24). Furthermore, it has been shown that AVP is neither secreted nor destroyed by the renal tubules (25) and that AVP in adult urine is stable over long periods of time (1 9).…”
Section: Discussionmentioning
confidence: 99%
“…It could also be attributed to the assay systems employed by different workers but in our study a good correlation was ob tained between the results of bioassay and radioimmunoassay, suggesting that the anti serum did not cross-react with fragments of the AVP molecule in urine. A further possi bility is the lower glomerular filtration rate found in the newborn, as urinary AVP corre lates with creatinine clearance [6],…”
Section: Discussionmentioning
confidence: 99%
“…kg.24 h-' in the fetus and neonate, respectively. The rate of VP excretion in the fetus and newborn lamb is, thus, much higher on a body weight basis than the amount excreted by an adult human on a normal Na intake, and is in the range of values reported by Goddard et al (7) in the human neonates (6,10).…”
Section: Discussionmentioning
confidence: 49%
“…The use of urine for this purpose would offer the advantage of reducing the number and volume of blood samples as well as the need for a very sensitive assay because concentrations in the urine are usually higher than in the plasma. But, Robertson (14) reported that VP excretion varied more with solute excretion than plasma concentration and, in the newborn, Goddard et al (7) found that urinary VP is correlated with glomerular filtration rate. The purpose of the present study is to examine the factors associated with increased renal excretion of VP in the hypoxic fetus and newborn.…”
mentioning
confidence: 99%